State Dependence in Welfare Receipt: Transitions Before and After a Reform - Regina T. Riphahn; Christoph Wunder (Institute for the Study of Labor (IZA), 2015)
We study state dependence in welfare receipt and investigate whether welfare transitions changed after a welfare reform. Using data from the German Socio-Economic Panel, we apply dynamic multinomial logit estimators and find that state dependence in welfare receipt is not a central feature of the German welfare system. We find that welfare transitions changed after the reform: transitions from welfare to employment became more likely and persistence in welfare and inactivity declined. We observe a large relative increase in transitions from employment to welfare. Immigrants' responsiveness to the labor market situation increased after the reform.
Keywords: I38; J61; 330; social assistance; state dependence; unemployment benefit II; immigration; dynamic multinomial logit